Katechetyczne i psychologiczne aspekty przynależności do wspólnoty Kościoła w okresie wczesnej adolescencji - Kopiczko, Tomasz; Dacka, Monika (Verbum Vitae, 2024)
From the point of view of both catechetics and psychology the period of early adolescence raises many difficulties and at the same time poses a challenge for scientific reflection and educational practice. The aim of this article is to undertake an interdisciplinary reflection on belonging to the community of the Church of people in early adolescence. The results of the undertaken scientific research have made the aim possible to be fulfilled in three important aspects. Firstly, it is the characterisation of the period of early adolescence with regard to the need for belonging. Secondly, the social and cultural challenges that constitute the context of adolescence have been shown. The third element is the identification of concrete proposals for solutions aimed at the practice of faith education. Through the use of an analytical and synthetic method, a number of theological and psychological texts but also empirical studies have been examined. It allows us to develop conclusions and to point out the need for concern for proper personal relationships, sensitive support of young people, correct transference of experiences and care for a sense of community.